Electrochemical Reduction of CO2: Effect of Convective CO2 Supply in Gas Diffusion Electrodes. Issue 22 (18th November 2019) - Duarte, Miguel; De Mot, Bert; Hereijgers, Jonas; Breugelmans, Tom
Abstract: The electrochemical reduction of carbon dioxide (CO2 ) is a promising technology in light of energy transition and industrial electrification. In this study, two different electrolyzer configurations, flow‐through and flow‐by modes, were analyzed for the production of carbon monoxide to resolve the CO2 mass‐transfer limitation problem at high current densities in gas diffusion electrodes. These two configurations respectively state convective and diffusive flow inside the gas diffusion layer, and their effect was studied on the cathodic performance of the electrolyzer by varying the operating conditions: cathodic potential, electrocatalyst loading, and Nafion content. In flow‐through configuration, a current density of 220 mA/cm 2 could be achieved at a faradaic efficiency of 90 %; whereas, in the flow‐by configuration, the current density was at the same faradaic efficiency limited to 140 mA/cm 2 . However, the flow‐through configuration has a few limitations, such as lower energy efficiency, owing to the higher ohmic drop and the faster deactivation caused by crystallization of electrolyte salts inside the gas diffusion electrode. Therefore, flow‐by mode is currently the most adequate configuration for the long‐term operation of electrolyzers for the reduction of CO2 to CO. This study represents an essential step toward the application of electrolyzers for the electroreduction of CO2 . Abstract : Go with the flow : Two different CO2 electrolyzer configurations, flow‐through and flow‐by modes, are analyzed for the production of carbon monoxide to resolve the CO2 mass‐transfer limitation problem at high current densities in gas diffusion electrodes. In the flow‐through configuration, a current density of 220 mA/cm 2 can be achieved at a faradaic efficiency of 90 %; whereas, in the flow‐by configuration the current density is at the same faradaic efficiency limited to 140 mA/cm 2 .